A tale of two kitties : a magical cats mystery - Kelly, Sofie, 1958- (Kelly, Sofie, 1958- Magical cats mystery., 2017)
With a well-placed paw on a keyboard or a pointed stare, Kathleen's two cats, Hercules and Owen, have helped her to solve cases in the past- so she has learned to trust their instincts. But she will need to rely on them even more than ever when a twenty-year-old scandal leads to murder... The arrival of the Janes brothers has the little town of Mayville Heights buzzing. Everyone of a certain age remembers when Victor had an affair with Leo's wife, who then died in a car accident. Now it seems the brothers are trying to reconcile, until Kathleen finds Leo dead. The police suspect Leo's son, Kathleen's good friend Simon, who had a furious argument with his father and now has an alibi no one can verify. To prove her friend innocent, Kathleen will have to dig deep into the town's history- and into her sardine cracker supply, because Owen and Hercules don't work for free...